The impact of Hudson‐Bergen Light Rail on residential property appreciation. (22nd May 2013) - Kim, Kyeongsu; Lahr, Michael L.
Abstract: This paper analyses the impact of the Hudson‐Bergen Light Rail (HBLR) on residential property prices. Unlike similar studies that use a hedonic model with cross‐sectional data, this one uses repeat‐sales data of properties that sold at least twice between 1991 and 2009. It shows how proximity to the nearest HBLR station, relative accessibility gains across stations, and anticipation of the commencement date of the HBLR station influence home price change. Our results show that properties near the two commuting stations farthest from the revitalized central business district experienced high appreciation. It also reveals that different accessibility gains across areas were produced based on the availability of existing public transportation options. Using a negative–exponential gradient, we find that these higher appreciation rates tended to dissipate about 1/4 mile (402 m) from stations. This supports that properties around urban commuting stations enjoy higher marginal benefits through improved transit accessibility and reduced transportation costs as Alonso's model predicts.